2022
DOI: 10.1007/s42729-022-00873-1
|View full text |Cite
|
Sign up to set email alerts
|

Traditional, Modern, and Molecular Strategies for Improving the Efficiency of Nitrogen Use in Crops for Sustainable Agriculture: a Fresh Look at an Old Issue

Abstract: Reactive nitrogen (N) plays a pivotal role in supplying N to plants and soil microbes, but it has negative environmental impacts through influencing the quality of water and air, which in turn influences human health. Thus, there is an urgent necessity to maximize N benefits while reducing the negative impacts on the environment. Improving crop N use efficiency (NUE) is required for environmental conservation and agricultural sustainability. Thus, the pivotal objective of this article is to introduce the moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 264 publications
0
2
0
Order By: Relevance
“…The N-difference method is based on the difference in N-uptake between a crop that receives a specific amount of N and a reference plot without applied N ( Cassman et al., 2002 ). It is a suitable index for research contexts because: i) it considers background soil N contents by accounting for N uptake or production in unfertilized plots, and ii) it is a simple and cost-effective method ( Elrys et al., 2022 ). The majority of studies reported N use efficiency based on the total aboveground N uptake in fertilized and unfertilized plots; however, there is a lack of information on N deposition and fixation needed to determine total N inputs.…”
Section: Methodsmentioning
confidence: 99%
“…The N-difference method is based on the difference in N-uptake between a crop that receives a specific amount of N and a reference plot without applied N ( Cassman et al., 2002 ). It is a suitable index for research contexts because: i) it considers background soil N contents by accounting for N uptake or production in unfertilized plots, and ii) it is a simple and cost-effective method ( Elrys et al., 2022 ). The majority of studies reported N use efficiency based on the total aboveground N uptake in fertilized and unfertilized plots; however, there is a lack of information on N deposition and fixation needed to determine total N inputs.…”
Section: Methodsmentioning
confidence: 99%
“…The NUE indices refer to key metrics used to assess the effectiveness with which plants utilize nitrogen in their growth and development (2,3). These indices help measure the efficiency of nitrogen uptake, assimilation, and utilization by plants, which is crucial for optimizing fertilizer application and reducing environmental impacts such as nitrogen leaching and greenhouse gas emissions (4)(5)(6). According to Congreves et al (7), the common NUE indices include nitrogen uptake efficiency (NUpE), nitrogen utilization efficiency (NUtE), and nitrogen recovery efficiency (NRE).…”
Section: Introductionmentioning
confidence: 99%